Characterization and Comprehensive Evaluation of Phenotypic and Yield Traits in Salt-Stress-Tolerant Peanut Germplasm for Conservation and Breeding - Nan Zhang; He Zhang; Jingyao Ren; Baiyi Bai; Pei Guo; Zhenghao Lv; Shuli Kang; Xinhua Zhao; Haiqiu Yu; Tianhong Zhao (Horticulturae, 2024)
Salt stress is a limiting factor affecting the growth, development, and yield of peanuts. Breeding improvement is a possible solution to overcome salt stress. The salt tolerance of 57 peanut cultivars in Northeast China was identified using indoor simulation at the germination stage, the seedling stage, and field natural identification. At the germination stage, 75 mM NaCl was the most suitable screening concentration, and the seed vitality index of 57 cultivars was analyzed using the membership function and cluster analysis. Among these cultivars, 11 were identified as salt-tolerant and 19 were salt-sensitive during germination. In the seedling stage, six salt tolerance coefficients (STCs) showed significant correlation. A gray relational analysis was used in combination with evaluation grading, resulting in the identification of 14 salt-tolerant cultivars and 12 salt-sensitive cultivars. In the field screening, a comprehensive analysis was conducted using a principal component analysis of nine indices, including agronomic characteristics, yield characteristics, and SPAD. This analysis led to the determination of three comprehensive indices. The weighted membership function was used for comprehensive evaluation. Finally, three salt-tolerant cultivars and four salt-sensitive cultivars suitable for planting in Northeast China were screened out to provide an excellent germplasm for researching the salt-tolerant mechanism of peanuts.